Manual of Child Psychology.
DOI: 10.1037/10756-011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on mental development.

Abstract: The studies reported in this chapter are based primarily upon results from the use of standard intelligence tests. The influence of environment on mental ability will therefore, in the first instance, be observed only through its effect upon mental test scores. The validity or general significance of such scores rests upon the extent to which they serve as indicators of a wider range of adaptive behavior (that is, of mental capacities or potentialities). No test is as valid as we would like to have it, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 146 publications
0
12
0
Order By: Relevance
“…They concluded that learners born in the warmer months obtained slightly higher scores than those born in the colder months. On his part, Fitt (1941) found that the intelligence of the Autumn born children was more often found to be higher, and the safest procedure was to regard the summerautumn as the high level period, while Jones (1954) concluded that the season of birth with the highest level of I.Q. was either the spring or summer.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They concluded that learners born in the warmer months obtained slightly higher scores than those born in the colder months. On his part, Fitt (1941) found that the intelligence of the Autumn born children was more often found to be higher, and the safest procedure was to regard the summerautumn as the high level period, while Jones (1954) concluded that the season of birth with the highest level of I.Q. was either the spring or summer.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most of the early studies found no relationship at all between tests in infancy and I.Q_. results obtained during the school age period (Anderson, 1939;Bayley, 1949;Jones, 1954). However, these entirely negative findings may have been due to various methodological deficiencies (Thomas, 1967), in particular to an excessive reliance on purely motor items and the use of samples of children nearly all of whom were of well above average intelligence.…”
Section: Intellectual Developmentmentioning
confidence: 99%
“…(3) The greater similarity of MZs compared with DZs is probably caused by additional environmental variance induced by the greater physical resemblance of the MZs (e.g ., Jones, 1949).…”
Section: Old Heritability Estimates 177mentioning
confidence: 99%